A love like the sun - Neilson, Riss M. (Berkley Romance, 2024)
"Lifelong best friends spend a fateful summer discovering what might happen if they were to be something more in this radiant, heart-clenching adult debut. Laniah Thompson is a homebody who craves privacy. Issac Jordan is internet famous and spends his days followed by paparazzi. She runs a small business with her mom in her hometown. He runs an international brand. And they've been best friends since childhood. When Issac comes home to Providence for the first time in months and discovers Laniah's dream is slipping out of reach as she and her mom struggle to pay the bills at Wildly Green, their natural hair store, she refuses to take a dime from him. And so, he does what any self-respecting best friend would do: tells the world they're dating. Suddenly business is booming, and Laniah agrees to his ridiculous plan to pretend to be lovers for the course of the summer. Just long enough to catch the eye of an investor and get her dream back on track, like she helped him do so many years ago, he reminds her. Too soon, though, Laniah knows she's playing with fire, because for as long as they've been friends there's an undeniable pull they've never given in to. And as the lines between art and life--real and pretend--blur, it becomes harder and harder to see where friendship ends and something else begins.... Told over the course of three sizzling summer months, A Love Like the Sun is about shared history, those who make us our bravest selves, and love in its many forms"--